Is there a Relationship Between Sleep Apnea and Central Corneal Thickness?. (November 2013) - Ekinci, Metin; Huseyinoglu, Nergiz; Cagatay, H. Huseyin; Ceylan, Erdinc; Keles, Sadullah; Gokce, Gokcen
Abstract Purpose: The objective of this study was to determine the central corneal thickness (CCT) measurements in patients with Sleep Apnea Syndrome (SAS) and the relationship between the severity of SAS and minimal arterial oxygen saturation (min. SpO2) with respect to CCT. Materials and methods: Two hundred and fourteen eyes of 107 patients (58 males, 49 females) who were diagnosed as SAS and 80 eyes of 40 healthy subjects (20 males, 20 females) were included in the study. The SAS patients were divided into subgroups according to their Apnea–Hypopnea Index (AHI) values as: AHI values between 5 and 15 as subgroup 1, between 15 and 30 as subgroup 2, and the values ≥30 as subgroup 3. The CCT was measured by an ultrasonic pachymetric system. Statistical analyses were an analysis of variance test and, for post-hoc analysis, the Dunnett C test. Results: Mean age was 52.5 ± 10.96 years in the study group, and 40.7 ± 10.14 years in the control group. There were 58 (54.2%) males and 49 (45.8%) females in the study group, and 20 (50%) males and 20 (50%) females in the control group. Mean CCT values were 526.65 ± 25.06, 525.26 ± 29.25, 512.93 ± 43.20 and 539.90 ± 17.28 in subgroup 1, subgroup 2, subgroup 3 and the control group, respectively. There were no statistically significant differences between gender and age groups with respect to CCT (p > 0.05). When the mean CCT values of each subgroups were compared with the control group, the differences were statistically significant (p < 0.05). There was a negative correlation between CCT and AHI values and a positive correlation between CCT and min. SpO2 values. Conclusions: CCT measurements differ significantly in patients with SAS compared with healthy control subjects. It should be taken into consideration that SAS may reduce CCT over time and that CCT should be measured in each ophthalmic examination.